Analisis Perancangan Konstruksi Galian Berturap Pada Tanah Pasir - Harrisla, Arrevan M.; Yuliet, Rina (Jurnal Bangunan, Konstruksi & Desain, 2024)
Braced cuts are sheet piles built on excavations made for the construction of foundations that are quite deep and the sides of the excavation are vertical. The vertical surface of the excavation requires protection with a temporary sheet pile installation system to avoid collapse that may occur together with the subsidence or collapse of the bearing capacity of the surrounding foundation. In sheet pile excavation work, failures often occur in the work, one of which is the collapse of the sheet pile excavation, this can cause very large financial losses and even claim lives. One of the causes of collapse in sheet pile excavations is because the dimensions of the sheet pile excavation are too slender so that they are unable to withstand active soil pressure when saturated with water. The purpose of this study was to obtain sheet pile and support specifications, the actual depth of sheet pile pile driving, deformation and displacement in the sheet pile and support. From the results of the sheet pile design analysis, the sheet pile cross-section modulus value was obtained as 1575.1 cm3/m, so that the U-type sheet pile specification with a type IIIA cross-section was obtained. The axial capacity of the support is 2542.115 kN, which is greater than the largest force of 1003.975 kN, so that the support capacity can be used. The actual depth of the excavation sheet pile is 9.5 m and the total length of the sheet pile is 19.5 m.